Differentiation instruction publications in physical education: bibliometric analysis of the last ten years - Blegur, Jusuf; Hardiansyah, Sefri (Journal of Education and Learning (EduLearn), 2024)
Research and publications on differentiation instruction in various subjects have developed rapidly in the world. Unfortunately, this trend is not directly proportional to the subject of physical education, even though differentiation instruction is the latest learning trend that is based on student learning needs. This research aims to analyze the metrics and visualization of differentiation instruction publications over the last ten years (2013-2023) using the literature review method. Google Scholar inspection using the Publish or Perish application only found nine articles (out of 16 articles) that met the VOSviewer visualization analysis criteria. As a result, the highest publication metrics were only three articles in 2014 and 53 citations as the highest top citations in 2019 for two articles. Network term differentiation is limited to three terms: analysis, lesson, and education. The VOSviewer visualization confirms that differentiation instruction has great potential to be developed in physical education to contribute to fulfilling students' learning experiences by their learning potential preferences. Future research can consider aspects of differentiation instruction that are not limited to teachers evaluating student learning outcomes based on differentiation instruction, and using differentiation instruction to improve various skills that help students survive in real life.